Identification of a pyroptosis-related prognostic model for colorectal cancer and validation of the core gene SPTBN5 - Guangyao Li; Pingyu Wang; Xiangnan Feng; Yongxiang Li (Discover Oncology)
Abstract Background Pyroptosis, an emerging type of programmed cell death. The mechanisms of pyroptosis mainly include inflammasome-activated pyroptosis and non-inflammasome-activated pyroptosis. Multiple prognostic scoring systems that utilize pyroptosis-related gene expression have been validated as effective predictors of patient outcomes. But the relationship between pyroptosis and colorectal cancer remains unclear. This study has established a gene signature associated with pyroptosis to forecast the prognosis of CRC patients. Methods An analysis of 52 pyroptosis genes was conducted in both CRC and normal colorectal tissues, leading to the discovery of differentially expressed genes (DEGs). Core pyroptosis-related genes were identified using least absolute shrinkage and selection operator (LASSO) Cox regression to establish a prognostic risk score (PRS) for predicting CRC patient outcomes. The TCGA cohort was split into high-risk and low-risk groups based on the PRS, followed by Gene Ontology (GO) and KEGG pathway analyses. Additionally, differences in the enrichment scores of 16 immune cell types and the activity of 13 immune-related pathways were compared. The role of SPTBN5, a core pyroptosis-related gene, was validated through functional experiments on human colorectal adenocarcinoma cells (SW480). Results 40 differentially expressed genes were identified from 52 pyroptosis genes. A risk model was subsequently developed using 25 core pyroptosis-related genes identified through LASSO Cox regression analysis, and this model was validated in GEO cohorts. GO and KEGG pathway analyses showed that the DEGs are predominantly associated with mineral absorption, thyroid hormone synthesis, and pancreatic secretion. Functional experiments demonstrated that down-regulation of SPTBN5 expression through transfection led to significant decreases in the proliferation, migration, and clonogenicity of SW480 cells. Conclusion The PRS can identify high-risk CRC patient groups and predict patient prognosis. SPTBN5 may present a potential therapeutic target for CRC.